THE SOPHOMORES’ PERCEPTION ON THE PRONUNCIATION PRACTICE COURSE - Irfan Hamonangan Tarihoran (Jurnal Riset Kajian Teknologi dan Lingkungan, 2018)
This paper aims at describing the 15 sophomore’s perception on the pronunciation practice at STKIP Paracendekia NW Sumbawa. The research adopts qualitative method with descriptive method. To obtain data, questionnaires, pronunciation test, and observation are applied. Twelve items of closed-ended questions are distributed to the participants. The study reveals that the participants encounter difficulty in pronunciation practice since their lack of phonetics ability. Specifically, they consider vowel sounds more difficult to practice than the consonant ones. Besides, the phonemes /3/and /?/ are found to be the most difficult vowel sounds to practice whereas the phonemes /?/ and /ð/ are the most difficult consonant ones. Meanwhile, their common techniques used during learning the course as well as the lecture’s method are considered helpful even though some more development is required. Furthermore, the sophomores are expected to increase their frequency of use of a standardized-IPA (International Phonetics Association)-dictionary and focus on a certain English variant.